RELATIONSHIP BETWEEN SALINITY AND THE 3H-3HE AGE IN DEEP WATER OF LAKE BAIKAL - Shimaraev M.N.; Gnatovskii R.Yu.; Blinov V.V.; Zhdanov A.A. (My University, 2006)
The application of chemical tracers (freon and helium/tritium ratio) in the 1990s made it possible to date Baikal water at different depths by the timing of its contact with the atmosphere. The age increases with depth from 0.5–4 yr in the upper 300–400 m to 10–18 yr at 200–500 m above the bottom. The age is variable in different years in the near-bottom zone. The cause of water aging with depth is the relaxation of processes responsible for its interaction with water of upper layers. Free temperature convection and currents foster active water mixing down to the depth of 300–400 m. In deeper layers where free convection is missing and currents are weakened, the activity of water exchange with upper layers decreases. Approaching the bottom, the activity increases again under the influence of deep (forced) temperature convection, near-slope circulation at the thermobaric field front, and the current field [4]. Consideration of datings made it possible to calculate the time of deepwater renewal (8–10 yr), the rate of vertical water exchange, and the value of “new” production.
Keywords: Baikal